Maintainability for Object Oriented Software System using AHP - Amit Sharma, Prof. (Dr.) Prabhat Kumar Vishwakarma (International Journal of Advanced Science and Technology, 2020)
As of late to achieve impressive accomplishment in programming framework, viability assumes an exceptionally urgent part and fundamental quality attributes may be considered. This paper describe practicality display that can help to proposed to look at the fundamentals of question arranged programming framework. Endeavors have been made on programming created in various programming dialects to influence examination of viability to design and analyzing of Analytic Hierarchy Process using the help of Fuzzy Index strategy.